UHG-based Mutation Screening in Type 2B von Willebrand’s Disease: Detection of a Candidate Mutation Ser547Phe - Wood, Nigel; Standen, Graham R; Bowen, Derrick J; Cumming, Anthony; Lush, Christopher; Lee, Richard; Bidwell, Jeffery (Thrombosis and Haemostasis, 1996)
We have recently described a novel mutation screening technique for the diagnosis of type 2B von Willebrand’s disease (vWD). Analysis involves the use of a synthetic universal heteroduplex generator (UHG). To test the validity of the technique, we have applied UHG screening to seven type 2B vWD patients of previously unknown genotype. Characteristic heteroduplex patterns for Arg543Trp and Val553Met mutations were found in three patients and one patient, respectively. A fifth patient gave a novel pattern and direct sequencing revealed a hitherto unreported candidate mutation (Ser547Phe) 8 bases downstream of an “identifier” deletion in the UHG molecule. The two remaining patients gave normal heteroduplex patterns; an Arg578Gln mutation was identified by PstI digestion in one individual and no mutation could be identified in the sequence covered by the UHG in the final patient. Using a combination of UHG technology and restriction analysis, over 85% of type 2B vWD patients can be rapidly diagnosed by genotype.